2016
DOI: 10.1097/tp.0000000000000861
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Adjuvanted Versus Nonadjuvanted Influenza Vaccine in Kidney Transplant Recipients

Abstract: Adjuvanted vaccine was safe and had similar immunogenicity to standard vaccine in the overall transplant cohort but did show a potential immunogenicity benefit for the 18 to 64 years age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 35 publications
4
65
0
1
Order By: Relevance
“…According to previous studies, the immunogenicity of influenza vaccine is reduced in SOT recipients, with up to 15-70% of patients failing to respond to the vaccine, depending on the organ transplanted, the immunosuppressive regimen, and the time of vaccination after transplant [29][30][31][32][33]. In our study, previous administration of induction therapy had no impact on the influenza vaccine response (humoral and cellular) even though the CD4+ cell count was lower in the group that had received ATG.…”
Section: Discussionmentioning
confidence: 51%
“…According to previous studies, the immunogenicity of influenza vaccine is reduced in SOT recipients, with up to 15-70% of patients failing to respond to the vaccine, depending on the organ transplanted, the immunosuppressive regimen, and the time of vaccination after transplant [29][30][31][32][33]. In our study, previous administration of induction therapy had no impact on the influenza vaccine response (humoral and cellular) even though the CD4+ cell count was lower in the group that had received ATG.…”
Section: Discussionmentioning
confidence: 51%
“…The major findings of our study were as follows: (1) for influenza A, which is comparable with seroconversion rates after influenza vaccination in this population. [35][36][37][38][39] In addition, the poor HI antibody response in transplant recipients has important methodologic implications for epidemiologic studies. The fact that there is a hyporesponsive subpopulation among transplant recipients, which does not develop HI antibodies in response to influenza vaccination or to natural infection explains the difficulties that have been experienced so far in finding clearly superior alternative vaccine strategies compared to the standard vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized trial of MF59-adjuvanted influenza vaccine in kidney transplants showed that this vaccine had similar immunogenicity to unadjuvanted vaccine. In this study, persons aged C 65 years had significantly diminished vaccine immunogenicity; after this group was excluded from the analysis, a subgroup analysis of patients aged 18-65 years showed that the adjuvanted vaccine performed better than standard vaccine [82]. In adult allogeneic HSCT patients, another randomized control trial using MF59, done by Natori et al, also found that adjuvanted vaccine demonstrated similar immunogenicity to non-adjuvanted vaccine [83].…”
Section: Influenza Vaccinementioning
confidence: 60%